2015
DOI: 10.6026/97320630011460
|View full text |Cite
|
Sign up to set email alerts
|

Design of a predicted MHC restricted short peptide immunodiagnostic and vaccine candidate for Fowl adenovirus C in chicken infection

Abstract: Fowl adenoviruses (FAdVs) are the ethiologic agents of multiple pathologies in chicken. There are five different species of FAdVs grouped as FAdV-A, FAdV-B, FAdV-C, FAdV-D, and FAdV-E. It is of interest to develop immunodiagnostics and vaccine candidate for Peruvian FAdV-C in chicken infection using MHC restricted short peptide candidates. We sequenced the complete genome of one FAdV strain isolated from a chicken of a local farm. A total of 44 protein coding genes were identified in each genome. We sequenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…This recent strategy has already proven its efficiency, firstly with the development of a vaccine against B serogroup Neisseria meningitidis [ 38 , 39 ]. Many studies have since been successfully conducted [ 40 43 ]. In this study, we have demonstrated the immune and protective powers against Campylobacter of four new antigens (YP437, YP562, YP9817, and YP9838) even if this was not statistically confirmed in a second experiment.…”
Section: Discussionmentioning
confidence: 99%
“…This recent strategy has already proven its efficiency, firstly with the development of a vaccine against B serogroup Neisseria meningitidis [ 38 , 39 ]. Many studies have since been successfully conducted [ 40 43 ]. In this study, we have demonstrated the immune and protective powers against Campylobacter of four new antigens (YP437, YP562, YP9817, and YP9838) even if this was not statistically confirmed in a second experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The FAdV-4 strain was isolated and characterized as a novel genotype [ 24 , 26 ]. Although many studies have been conducted on inactivated or recombinant subunit vaccines consisting of several serotypes of FAdVs against the conventional FAdV-4 strains [ 32 , 33 , 34 , 35 , 36 , 37 ], no vaccine has been developed and evaluated for the HPS associated with the novel hypervirulent FAdV-4 [ 26 , 38 ]. In this study, an inactivated novel genotype FAdV-4 vaccine formulated with oil-emulsion was developed, and the immune responses and protective efficacy were evaluated by challenging SPF chickens with a lethal dose of the novel hypervirulent FAdV-4.…”
Section: Discussionmentioning
confidence: 99%
“…In this urgent race to develop a vaccine, immunoinformatic techniques represent a powerful approach that allows the screening of whole pathogen proteomes to identify potential immunogenic regions ( 55 ). This includes predicting linear epitopes potentially presented by the Human Leukocyte Antigen (HLA) class I and II, which can be used to design peptide vaccines ( 56 ) and molecular diagnostic tests ( 57 ). The state-of-the-art programs are based on artificial neural networks ( 58 61 ), and they require both the sequence of target protein(s) and the host HLA allele(s) at 4-digit resolution ( 62 , 63 ).…”
Section: Introductionmentioning
confidence: 99%